The Impact of Educational Facilities on Student Motivation in Elementary School - Akmal, Fauzi; Taqiyuddin, Muhammad Fikri (Khalifa Journal of Islamic Education, 2024)
This study aims to determine the effect of facilities and infrastructure (x) on student learning motivation (y). This study is a quantitative study using a product moment analysis research design. The data collection techniques used in this study were questionnaires and documentation. The subjects in this study were all 57 students in grades IV-VI. Data analysis was performed manually using Microsoft Excel and SPSS 26 software. The results of this study are as follows: i) The facilities and infrastructure available in elementary schools are considered good, as indicated by a mean or average score of 46.7, which falls within the 45-51 interval, with a standard deviation of 4.62, representing a result of 56%. ii) The learning motivation of elementary school students is classified as poor, as seen from the mean or average value of 46 with a standard deviation of 5.24, which is presented as a result of 44%. iii) There is an influence between the facilities and infrastructure variable (x) and student learning motivation (y) based on the simple linear regression formula. The data obtained shows a sig of 0.000<0.05 (5% significance level), so Ha is accepted and Ho is rejected. Furthermore, based on data analysis, it is known that there is an R Square of 0.355 x 100% = 35.5%. This indicates that there is an influence between facilities and infrastructure (x) on learning motivation.